From Rebuke to Consolation Exegesis and Theology in the Liturgical Anthology of the Ninth Av Season - Stern, Elsie (Brown Judaic Studies, 2020)
This book contributes to the ongoing research into the emergence of rabbinic Judaism in the synagogue setting through a study of one constellation of rabbinic and synagogue literature, the sequence of prophetic lectionary texts designated for the Sabbaths surrounding Tisha b' Av, and the midrashirn, piyyutim and targumic texts that interpret them. An analysis of this literary constellation allows us to better understand two dynamics that are relevant to the discussion of the development of rabbinic Judaism in the late antique synagogue: a) the relationship between the rabbinic Judaism that was propagated in the synagogue and the non-rabbinic synagogue culture that the rabbis encountered and interacted with there; b) the relationship between rabbinic literature that was composed by sages for their rabbinic colleagues and students, and rabbinic literature that was directed toward a wider Jewish lay audience as it was imagined by the rabbis.